Analisis Penerimaan Pengguna Terhadap Penggunaan Sistem Surat Manajemen Elektronik Menerapkan Model UTAUT - Rifat Hafiz Aditya; Asif Faroqi; Anita Wulansari (STMIK Budi Darma, 2023)
SISMADU is a web-based application service that is used to send letters electronically. In implementing the use of SISMADU there are several units that do not utilize applications in electronic mail services. But on the other hand this application is applied by various units on an ongoing basis. This research was conducted with the aim of knowing the factors that influence user behavior in the use of an integrated incoming mail information system as a media for electronic mail services at the Haji Regional General Hospital in East Java Province using the Unified Theory of Acceptance and Use of Technology (UTAUT). involving performance expectancy, effort expectancy, social influence, facilitating condition, behavioral intention, and use behavior variables. The population in this study is system users as many as 70 users. The sampling technique used is saturated sampling, because it involves the use of all members of the population as a sample. Data was obtained by distributing questionnaires to application users, data were analyzed using SEM-PLS. After conducting a thorough data analysis, it can be concluded that based on these findings, there are conclusions that can be drawn, namely the discovery of factors that significantly influence behavioral intention, namely performance expectations and business expectations. Meanwhile, social influence factors were found to have no significant effect on behavioral intention. Then, factors that significantly influence use behavior include behavioral intention and facilitating condition factors